Successful Treatment of Pantoea agglomerans Bacteremia Using Oral Antibiotics - Megan Penner; Brittany Romans; Lauren Tah; Brianna Argubright; Matthew Strohmeyer (Case Reports in Infectious Diseases)
A 30-year-old female with a medical history of gastrointestinal reflux and intravenous methamphetamine use was admitted to the hospital with complaints of fever and chills. Pantoae agglomerans was isolated in one out of two blood cultures. Although information was limited about the duration and efficacy of oral antibiotics to treat this type of infection, the patient recovered with oral antibiotic treatment following a short course of intravenous antibiotics.